2019
DOI: 10.1021/acs.jmedchem.9b00316
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-(Indol-5-yl)-indazole Derivatives as Novel Myeloid Differentiation Protein 2/Toll-like Receptor 4 Antagonists for Treatment of Acute Lung Injury

Abstract: Acute lung injury (ALI) is often caused by systemic inflammatory responses. Targeting the myeloid differentiation protein 2/toll-like receptor 4 (MD2–TLR4) complex may be a promising way to treat Gram-negative bacterial-induced inflammatory disorders. In this study, we report the design and synthesis of a new series of 3-(indol-5-yl)-indazoles, which were evaluated for their anti-inflammatory activities in macrophages. Among the analogues generated, the promising 3-(indol-5-yl)-indazole analogue 22m inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 53 publications
(103 reference statements)
1
36
0
Order By: Relevance
“…Studies have shown that LPS promotes the excessive production of in ammatory mediators by activating the TLR4/Myd88 signaling pathway, leading to lung damage and ALI progression [27,28]. Recent studies have shown that several natural products modulate the in ammatory response by inhibiting the TLR4/NF-κB signaling pathway [29][30][31][32][33]. Our results showed that astaxanthin inhibit the TLR4/MyD88/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have shown that LPS promotes the excessive production of in ammatory mediators by activating the TLR4/Myd88 signaling pathway, leading to lung damage and ALI progression [27,28]. Recent studies have shown that several natural products modulate the in ammatory response by inhibiting the TLR4/NF-κB signaling pathway [29][30][31][32][33]. Our results showed that astaxanthin inhibit the TLR4/MyD88/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 59%
“…[31][32][33] LG4, a novel indole compound developed in our laboratory, has been shown to exert anti-inflammatory effects both in vitro and in vivo. 34 In this study, we found that LG4 treatment remarkably reversed the function, histological abnormalities, fibrosis, and inflammation in the kidneys of T1DM mice without affecting their blood glucose and body weight. The effect of LG4 is highly related to its antiinflammation property.…”
Section: Discussionmentioning
confidence: 50%
“…How the availability of starting materials affects the SA can be seen by enumerating methylated variants of compound A ( 57 ) followed by an evaluation using ASKCOS’s retrosynthesis tree search. While an expert chemist can easily infer that compound A is disconnected by amide formation and C–C cross-coupling, the general knowledge of the commercial availability of the methylated starting materials is less likely.…”
Section: Section 2: How Is Casp Currently Used In the Pharmaceutical mentioning
confidence: 99%